THE YORÙBÁ NATIVE AIR TRADITION OF CHORAL MUSIC IN CHRISTIAN LITURGY 1920-1980 (2014)
Yoruba Native Air (YNA) tradition of choral music in Christian liturgy evolved as a result of the conflict which developed between European and Yoruba church music traditions at the inception of Christianity in Yorubaland. The growing body of scholarship on Nigerian choral music has, so far, only tangentially referenced the YNA tradition in spite of its being the foundation of Yoruba choral church music today. This study, therefore, investigated the history of the YNA tradition and undertook an ethnomusicological analysis of songs composed by three of its prominent composers between 1920 and 1980. The study employed the theory of interculturalismto foreground the socio-cultural circumstances that attended the evolution of the YNA tradition. Three distinguishedfirst generation YNA composers — Ola Olude, DayoDédẹkẹ́ and PópóọláDọ̀pẹ̀mú — who had sizeable published compositions were selected. Information was collected through In-Depth Interviews conducted with Dọ̀pẹ̀mú, while with the other two (now late), interview sessions were held with eight family members and associates. Four- Focus Group Discussions were held with specially selected former choir and church members who had first-hand experiences of these composers and their works. Biographical notes, church records,and one hundred and seventy-three songs were transcribed, classified and analysed. The activism and advocacy of the early YNA composers were manifestations of the cultural nationalism characteristic of the late 19th /early 20th centuries. They produced works which satisfied the musical, liturgical and spiritual needs of Yoruba Christians of that period. Whereas Dédẹkẹ́ studied music at the Trinity College, University of London, Olude and Dọ̀pẹ̀mú were largely self-taught under the influence of missionaries, indigenous organists and choirmasters. While Dọ̀pẹ̀mú and Dédẹkẹ́ are the archetypes of the harmonic and structural frameworks of the YNA tradition, Olude believed in unisonous singing. Noticeably, Dọ̀pẹ̀mú showed greater versatility and skill in harmonic choral composition and organ playing. In their itinerancy, they composed, taught and performed across several congregations. YNA compositions were classifiedfrom the perspectives of their sources, styles and liturgical functions. The compound quadruple and duple woro rhythm is the primary rhythm of the YNA tradition, while the secondary rhythm is the simple quadruple diasporicrhumba rhythm, all played on akuba drums. YNA compositions utilised the African call and response formula through the solo-chorus and unison-chorus modes. As an intercultural music tradition, YNA successfully resolved the conflict that was generated between European and Yoruba music traditions at the inception of Christianity in Yorubaland. The YNA tradition has produced a dynamic intercultural idiom both at the material and ideational levels of church music. Hence, there is an urgent need to document its numerous composers’ works in western notation in order to make them accessible to more users. Having employed standard musicological parameters for identifying and defining songs in the YNA choral mode, this study provides a prescriptive framework that could be adopted by future YNA composers.